2019
DOI: 10.1242/bio.039453
|View full text |Cite
|
Sign up to set email alerts
|

Soft substrate maintains proliferative and adipogenic differentiation potential of human mesenchymal stem cells on long-term expansion by delaying senescence

Abstract: Human mesenchymal stem cells (hMSCs), during in vitro expansion, gradually lose their distinct spindle morphology, self-renewal ability, multi-lineage differentiation potential and enter replicative senescence. This loss of cellular function is a major roadblock for clinical applications which demand cells in large numbers. Here, we demonstrate a novel role of substrate stiffness in the maintenance of hMSCs over long-term expansion. When serially passaged for 45 days from passage 3 to pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 51 publications
4
59
0
Order By: Relevance
“…Surface morphology associated with cell adhesive ligands is beneficial for stem cells spreading. Especially, topography of the surface enhances the differentiation of hMSCs toward osteogenic and adipogenic lineage . Previous studies have suggested that the combined micro‐ and nanoscale topography is favoring hMSCs proliferation and differentiation .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Surface morphology associated with cell adhesive ligands is beneficial for stem cells spreading. Especially, topography of the surface enhances the differentiation of hMSCs toward osteogenic and adipogenic lineage . Previous studies have suggested that the combined micro‐ and nanoscale topography is favoring hMSCs proliferation and differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…And yet, an enhanced spreading area is characteristic of a senescence state, in other words, an irreversible cell division arrest which makes the cells unsuitable for clinical use. This issue has been addressed and is still looking for a solution . In this part, we study two hydrogels: a system with PEG20000 having an average shear elastic modulus of around 600 Pa and a matrix with PEG6000 around twice as stiff, having an average shear elastic modulus of around 1400 Pa (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations